ÉTICA PROFESIONAL Y SU INCIDENCIA EN LA FORMACIÓN INTEGRAL DE LOS ESTUDIANTES DEL 8VO SEMESTRE DE LA CARRERA DE COMUNICACIÓN SOCIAL DE LA UNIVERSIDAD TÉCNICA DE BABAHOYO EXTENSIÓN QUEVEDO, AÑO 2022. - Lopez Litardo, Nurys Jessenia (2022)
Professional ethics is of vital importance for professional development, since it is part of the educational system, as it creates standards that help to know what is acceptable and what is not, therefore, ethics contributes to create an enabling environment for both students and teachers. Determining professional ethics and its impact on the comprehensive training of students in the eighth semester of the career of social communication of the Technical University of Babahoyo extension Quevedo, year 2022, depends largely on the training that the person has within the classroom, so this case study focuses on the need that the university community has on this issue, getting to use the survey instrument, to obtain the results of the case study, having as a result the lack of information on ethical content, since no training or workshops are provided within the institution, so that students can defend themselves in a working environment.